Survival patterns in lung and pleural cancer in Europe 1999–2007: Results from the EUROCARE-5 study. Issue 15 (October 2015) - Francisci, Silvia; Minicozzi, Pamela; Pierannunzio, Daniela; Ardanaz, Eva; Eberle, Andrea; Grimsrud, Tom K.; Knijn, Arnold; Pastorino, Ugo; Salmerón, Diego; Trama, Annalisa; Sant, Milena; EUROCARE-5 Working Group, 1
Abstract Background Survival of patients diagnosed with lung and pleura cancer is a relevant health care indicator which is related to the availability and access to early diagnosis and treatment facilities. Aim of this paper is to update lung and pleural cancer survival patterns and time trends in Europe using the EUROCARE-5 database. Methods Data on adults diagnosed with lung and pleural cancer from 87 European cancer registries in 28 countries were analysed. Relative survival (RS) in 2000–2007 by country/region, age and gender, and over time trends in 1999–2007 were estimated. Results Lung cancer survival is poor everywhere in Europe, with a RS of 39% and 13% at 1 and 5 years since diagnosis, respectively. A geographical variability is present across European areas with a maximum regional difference of 12 and 5 percentage points in 1-year and 5-year RS respectively. Pleural cancer represents 4% of cases included in the present study with 7% 5-year RS overall in Europe. Most pleural cancers (83%) are microscopically verified mesotheliomas. Survival for both cancers decreases with advancing age at diagnosis for both cancers. Slight increasing trends are described for lung cancer. Survival over time is higher for squamous cell carcinoma and adenocarcinomas than for small and large cell carcinoma; and better among women than men. Conclusions Despite the generalised although slight increase, survival of lung and pleural cancer patients still remains poor in European countries. Priority should be given to prevention, with tobacco control policies across Europe for lung cancer and banning asbestos exposure for pleural cancer, and in early diagnosis and better treatment. The management of mesothelioma needs a multidisciplinary team and standardised health care strategies.